Do chief sustainability officers and CSR committees influence CSR-related outcomes? A structured literature review based on empirical-quantitative research findings - Patrick Velte; Martin Stawinoga (Journal of Management Control, 2020)
Although an increasing amount of empirical research has been linked to the impact of management control and governance on corporate social responsibility (CSR) issues since the financial crisis of 2008/09, heterogeneous results have characterised this research field. Regarding the group level of corporate governance, the efficacy of board committees (e.g., audit, compensation or CSR committees) has been included in recent research designs. However, analyses of corporate governance at the individual level are related to the effects of top management members [e.g., chief executive officer (CEO), chief financial officer (CFO) or chief sustainability officer (CSO)] on CSR outcomes. This paper aims to convey a detailed understanding of sustainable management control's impact as CSR-related board expertise. In more detail, we focus on the influence of both CSR committees and CSOs on three CSR measures mainly analysed in empirical-quantitative research: (1) CSR reporting; (2) CSR assurance (CSRA); and (3) CSR performance. We motivate our analysis with increased relevance from practical, regulatory and research perspectives, and we employ a systematic literature review of the symbolic vs. substantive effects of sustainability-related board composition. Based on our theoretical model (legitimacy theory, stakeholder theory and upper-echelons theory), we selected 48 quantitative peer-reviewed empirical studies on this research topic. Our analysis shows that CSR committees positively influence CSR reporting and performance. Thus, there are indications that the implementation of a CSR committee is not a symbolic act, but instead substantively contributes to CSR activities. However, in light of inconclusive empirical research results and a lack of studies that have analysed CSO-related effects, a notable research gap has been identified. Moreover, we note the main limitations of prior research in this review and develop an agenda with useful recommendations for future studies.
Keywords: M41; M48; Q3; Q56; 330; CSR committee; Chief sustainability officer (CSO); CSR reporting; CSR performance; CSR assurance; Board expertise